Subjective assessments of research domain criteria constructs in addiction and compulsive disorders: a scoping review protocol - Ana Paula Ribeiro; Marcelo Piquet-Pessôa; Carina Félix-da-Silva; Julia Fernandes Eigenheer Mühlbauer; Juliana B de-Salles-Andrade; Leonardo F Fontenelle (BMJ Open, 2022)
Introduction Obsessive-compulsive and related disorders (OCRDs) and disorders due to addictive behaviours (DABs) are prevalent conditions that share behavioural and neurobiological characteristics. The Research Domain Criteria lists a series of constructs whose dysfunctions may be present in both groups of disorders. The present study will describe the research protocol of a scoping review of the literature on self-report scales and questionnaires that tap dysfunctional constructs that underlie OCRDs and DABs.Methods and analysis This protocol outlines a scoping review on self-report tools and questionnaires that assess OCRDs and DABs-related constructs. The scoping review will select sources in MEDLINE, EMBASE, PsychINFO and Web of Science databases. Inclusion and exclusion criteria will be designed according to the Population, Concept, Context, Types of source framework. Two reviewers will screen independently titles, abstracts and full texts to determine the eligibility of articles. A methodological framework including six stages steps ((1) identifying a research question; (2) identifying relevant studies; (3) study selection; (4) charting the data; (5) collating, summarising and reporting the result) will be used, and the findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist. Information extracted will be collated, and quantitative results will be presented using descriptive statistics such as percentages, tables, charts and flow diagrams as appropriate.Ethics and dissemination Ethical approval for conducting this scoping review is not required, as this study will involve secondary analysis of existing literature. The researchers will disseminate the study results via conference presentations and publication in a peer-reviewed journal.Scoping review protocol registration DOI 10.17605/OSF.IO/UJ7G5.